Behavior of low voltage networks in the presence of photovoltaic generation. - Villavicencio Gastelu, Joel (2021)
The impact of photovoltaic generation in the electrical network’ behaviour depends on the quantity of injected power. Thus, during the network analysis, all factor that could influence that power must be considered. In this paper, a methodology to analyse the network’ behaviour under the presence of photovoltaic generation is presented. The proposed methodology takes into account the stochastic nature of the photovoltaic insertion in the network via the Monte Carlo simulation method. In order to evaluate the influence of coincidence between PV generation and demand, a three-phase low-voltage network with residential and commercial users is considered. Simulations are performed along a day and considering several levels of photovoltaic penetration. Therefore, the proposed methodology can be used in operation planning studies performed by utilities